2017
DOI: 10.1002/ceat.201700067
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive 4D Flow Characterization in a Stirred Tank via Phase‐Contrast Magnetic Resonance Imaging

Abstract: A noninvasive quantification of the hydrodynamics in a stirred tank in space and time using flow-sensitive phase-contrast magnetic resonance imaging (PC-MRI) at 7 Tesla (7 T) is demonstrated. The PC-MRI technique is able to characterize the unsteady periodic 3D flow velocities with acceptable spatial and temporal resolution and does not imply that optically transparent fluids are employed. PC-MRI is already widely used for medical diagnostics in order to determine the blood flow velocities, e.g., for cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In physical experiments, many techniques, such as laser doppler velocimetry (LDV), particle image velocimetry (PIV), , double-tip conductivity probe, phase doppler velocimetry (PDA), magnetic resonance imaging (MRI), radioactive particle tracing (RPT), , electrical resistance tomography (ERT) , and positron emission particle tracking (PEPT), , were used to measure the velocity field and track the particle motion in the stirred tanks. They are all time- and cost-consuming, and the techniques used make it difficult to observe the microscopic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In physical experiments, many techniques, such as laser doppler velocimetry (LDV), particle image velocimetry (PIV), , double-tip conductivity probe, phase doppler velocimetry (PDA), magnetic resonance imaging (MRI), radioactive particle tracing (RPT), , electrical resistance tomography (ERT) , and positron emission particle tracking (PEPT), , were used to measure the velocity field and track the particle motion in the stirred tanks. They are all time- and cost-consuming, and the techniques used make it difficult to observe the microscopic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…A proof of concept on how phase‐contrast MRI can be used to study the flow inside a stirred tank is demonstrated by Janiga et al. 27. The method is also known as 4D phase‐contrast MRI and is often used in medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Within the different solvent systems, the requirements vary significantly, e.g., coalescence in a decanter is intended in a phase separation step in micellar and thermomorphic solvent systems whereas it should be prevented in nanoparticle‐stabilized emulsions where droplets are separated from the bulk phase by ultrafiltration. The measurement techniques used to monitor the swarm behavior, reaction performance and system characteristics range from (cryogenic) scanning electron microscopy (SEM) , and endoscopes and phase contrast magnetic resonance imaging (PC‐NMR) to inductively coupled plasma optical emission spectroscopy (ICP‐OES) , .…”
Section: Introductionmentioning
confidence: 99%